Characterization of an AX Compound Derived from Ti2SC MAX Phase. Issue 17 (23rd April 2019) - Hasegawa, George; Kawahara, Kei; Shima, Kazunari; Inada, Miki; Enomoto, Naoya; Hayashi, Katsuro
Abstract : Extraction of M elements from MAX phases results in " AX " compounds in contrast to the well‐defined two‐dimensional (2D) materials known as MX ene, which are prepared by the selective etching of A elements. Despite the extensive studies on MX ene from both experimental and computational aspects, the nature of the AX compounds still remains elusive, because the electrochemical etching of M atoms from MAX significantly spoils the crystal structure, predominantly resulting in amorphous AX products. Here, we demonstrate the characterization of an S/C complex prepared by the electrochemical etching of Ti2 SC. The spark plasma sintering (SPS) technique affords a well‐sintered Ti2 SC disk with high purity, which can be directly utilized as a binder‐free Ti2 SC electrode. It is found that the electrochemically extracted Ti elements in NH4 F electrolyte are partially crystallized into the monoclinic titanium oxynitride, TiO0.34 N0.74 . The formed amorphous S/C compound is classified into three components: acetone‐soluble volatiles including elemental sulfur, acetone‐insoluble volatiles, and non‐volatile species carbonizable into S‐doped carbon. Abstract : A/X Compound from MAX : Sulfur/carbon composites produced by the electrochemical etching of Ti atoms from Ti2 SC have been characterized in detail. The predominantly amorphous S/C compound can be classified into three components, most of which are active against the electrochemical lithiation and delithiation.